Studies of anthropometric and functional parameters of the referees of different skills in football - Abdula A.B (Kharkov National Pedagogical University, 2013)
The problems of functional training of arbitrators of different skills are considered. The study involved 12 referees for the highest, first and second league championship and the championship of Ukraine on football. The level of Simply-weights is studied. It was used the methodology of S.A. Dushanin. Revealed the results of anatomical and physiological condition of the body: heart rate, body temperature and body weight reduction referees during a soccer match. Found that the anthropometric characteristics and the length of body weight statistically significant differences between the arbitrators are not. It is noted that the weight of the arbitrators is markedly reduced during the game. The average weight loss during a major league game the referee is 2.67 kg in the first league of referees' weight decreased by 1.83 kg in the second league referees - is reduced by 1.92 kg. It is established that the level of functional training arbitrators league above the results of their younger colleagues.